New insights of the application of water or ethanol-water plant extract rich in active compounds in food - Plaskova, Anna; Mlcek, Jiri (Frontiers in Nutrition, 2023)
Plant extracts are becoming more used as food additives in various food systems due to their antioxidant abilities, which might prevent off-flavors in lipid-rich food and increase food products' shelf life. They might also improve nutritional and sensory properties because they contain active compounds such as polyphenols, vitamins, flavonoids, and other phytochemicals. This review summarizes the most recent literature about water or ethanol-water plant extracts used as flavors, colorings, and preservatives to fortify food and beverages. Extraction is an easy way to obtain active compounds from plants; also, using aqueous and ethanolic extracts is better for customer safety than toxic organic solvents. This study was performed with particular attention to describing the benefits of plant extract-fortified products such as meat, vegetable oils, biscuits, pastries, some beverages, yogurt, cheese, and other dairy products. Antioxidant-rich plant extracts can positively affect food safety by partially or fully replacing synthetic antioxidants, which have lately been linked to safety and health issues such as toxicological and carcinogenic consequences. On the other hand, the stability and distinct taste of liquid extracts limit their application in the food industry. There will be continuous development and a tendency to use these natural extracts, as indicated by the number of published works in this area, particularly in the past decade.